VELFÆRDSSTATENS SEMANTIK KOMPARATIVE OG TRANSNATIONALE PERSPEKTIVER - Béland, Daniel; Petersen, Klaus (Temp - tidsskrift for historie, 2014)
ABSTRACT The Semantics of the Welfare State: Comparative and Transnational Perspectives Social scientists, historians, and linguists have noted that the terms, metaphors, and concepts we use are far from innocent and are closely tied to political struggles and international exchanges. This is also the case when it comes to social policy. The words we use to make sense of social policy and the way we use them need to be properly studied to get the definitions right while grasping the political consequences of social policy language. But so far, little has been done in that respect. In this article, we argue that integrating the study of social policy language and concepts into mainstream comparative welfare state research is important and will open for new insights both in historical development of welfare states and what welfare states do. We point especially to two strands of literature as relevant point of departures for the study of social policy language. The first is the flourishing social science literature on the role of ideas in politics. The second is conceptual history. We illustrate the importance of studying social policy language by highlighting some of the results from a larger comparative project (Analysing Social Policy Language, Policy Press, 2014). That recent volume includes a number of comparative case studies of both nation states and transnational organizations and addresses questions such as: Which are the dominant social policy concepts and how are they contested? How did they become dominant and how does it relate to the institutional legacies of different types of welfare regime? Finally, we conclude the article by outlining a possible research agenda for the comparative study of social policy language.